Uji Kelayakan Ekonomi Proyek Rekonstruksi Jalan Sumbermujur Kabupaten Lumajang Berdasarkan Umur Rencana 10 Tahun - zanet valen; Amri Gunasti (Journal of Science and Engineering, 2026)
Road infrastructure is a vital component in supporting economic growth and regional connectivity. This study aims to analyze the economic feasibility of the Sumbermujur Road reconstruction project in Lumajang Regency valued at IDR 9,030,472,000 based on the Bill of Quantities (BOQ) with a 10-year design life. The analysis methods used include Net Present Value (NPV), Benefit Cost Ratio (BCR), Internal Rate of Return (IRR), and Payback Period (PP) at a discount rate of 7% per year. Project benefits were estimated based on vehicle operating cost (VOC) savings of IDR 821,250,000 per year and travel time savings of IDR 821,250,000 per year, yielding total annual economic benefits of IDR 1,642,500,000. The largest cost components in the BOQ are asphalt pavement works (45.19%) and structural works (36.61%). The analysis results show NPV = IDR 2,505,760,416 (positive), BCR = 1.28 (greater than 1), IRR = 13.09% (exceeding MARR of 7%), and Payback Period = 5.5 years (less than the design life). Based on all four indicators, the Sumbermujur road reconstruction project in Lumajang Regency is declared economically feasible for implementation.